THE USE OF DIRECTED READING THINKING ACTIVITY (DRTA) TO TEACH READING COMPREHENSION - Yatmini Yatmini; Siti Asiyah; Restu Mufanti (EDUPEDIA, 2017)
DRTA technique is a strategy that explain about teaching students in good reading habits. This strategy helps strengthen reading and critical thinking skill. The purpose of this research was to know the use of directed reading thinking activity (DRTA) to teach reading comprehension for the eleventh grade students in SMK Negeri 1 Poncol. The subject of this research was the students of the eleventh grade class XI Boga 2 of SMK Negeri 1 Poncol in the academic year 2017/2018, which consisted of 21 students. The research was started on July 26th, 2017 until August 1st, 2017. This Classroom Action Research was conducted in two cycles and each cycle consisted of two meetings. The researcher used three research instruments. They were: observation checklist, questionnaire, and test. Based on the result of this research, the observation checklist result showed that the students become active during teaching learning process. The result of observation checklist cycle 1 was 66.67%, while, the result improved up to 90.00% in cycle 2. The result of questionnaire in cycle 1 was 72.00%. While, the result of questionnaire in cycle 2 was 84.00%. It showed that the students enjoyed and were interested in reading comprehension. In cycle 1, there were 12 or 60.00% of students got score under KKM, and 8 or 40.00% of students passed in the test. Then, the students who reached the minimum score based of KKM in cycle 2 was 100%. Finally, the researcher concluded that the implementation of Directed Reading Thinking Activity (DRTA) Technique to Teach Reading Comprehension for the Eleventh Grade Students in SMK N 1 Poncol was successful. The researcher hopes that the result of this study will be useful for the next researcher.